Prolegomenon to the thought style of the new history of psychology - Pankalla, Andrzej; Kilian, Aleksandra (Studia Psychologica: Theoria et praxis, 2018)
The present article provides an introduction to the new history of psychology within the framework of critical perspective while offering some methodological solutions for contemporary historical research in psychology. We propose a new model of research for conducting studies in the history of psychology. This approach is predominantly concerned with reconstructing crypto thought styles, acknowledging the existence of peripheral sources of knowledge about human psychological life, and revealing hidden lines of inquiry, which will be presented using a contextual approach to the history of psychology. In this analysis, psychological knowledge will be treated as a product of social activities that occur un-der specific historical conditions and define the scope of psychological research. The proposed to examine history of psychology and investigative practice in a specific context will allow for deeper insight into the world’s history of psychology and provide new methods for studying psychological schools of thought and ideas established on the periphery of mainstream psychology. Finally, we offer words of encouragement for scholars engaging in a context-specific study of psychological thought and efforts made towards grasping the reality of a local soul.